Efektivitas Penurunan Kadar Besi (Fe) dan Kekeruhan pada Air Tanah dengan Penambahan Media Kulit Ubi Kayu (Manihot esculenta crantz) - Hendra Wijaya Sumakul; Andi Susilawaty; Habibi Habibi (Public Health Department, Universitas Islam Negeri Alauddin Makassar, 2020)
Since water is second most essential element in life after oxygen, the need of clean water never ceases. Clean water must meet certain criteria such as the chemical, physical and biological requirements. The iron content (Fe) in the water is one of the most crucial factors that determines whether the water is safe for use. Most of the residents of Lembo Sub district in Tallo District of Makassar City own wells from which they take the water for their daily use. Apparently, the water contains high level of iron (Fe) and turbidity. Some studies suggest that cassava peels (Manihot esculenta crantz) contain natural substances that can reduce the iron (Fe) content and turbidity of well water. For that reason, this research aims to examine the efficacy of cassava peels (Manihot esculenta crantz) in reducing the iron (Fe) content and turbidity of well water. In investigating the issue, this research used quasi experimental design with Completely Randomised Design (CRD) as the method. The results of statistical analysis suggest that cassava peels can significantly reduce the iron (Fe) content and turbidity of well water, as indicated by significance value of 0.022<0.05 and 0.015<0.05 respectively. The findings show the following statistics. The iron content in the well water before treatment is 5.59 mg/l. After a 15 cm cassava peel treatment, the iron content decreases to 0.03 mg/l on average (99.5%). After a 30 cm cassava treatment, the iron content decreases to 0.046 mg/l on average (99.2%), After a 60 cm cassava peel treatment, the iron content decreases to 0.28 mg/l on average (92%). As for the water turbidity, a 15 cm cassava peel treatment reduces the turbidity level by 1.18 NTU (97.4%), a 30 cm cassava peel treatment reduces the turbidity level by 3.6 NTU (92%), and a 60 cm cassava peel treatment reduces the turbidity level by 1.79 NTU (96.1%). Therefore, this research concludes that cassava peels significantly reduces the iron (Fe) content and turbidity of well water. Keywords: cassava peels, Iron content, turbidity, groundwater